Mapping of physics problem-solving skills of senior high school students using PhysProSS-CAT - Edi Istiyono; Wipsar Sunu Brams Dwandaru; Revnika Faizah (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2018)
Evaluation using computerized adaptive tests (CAT) is an alternative to paper-based tests (PBT). This study was aimed at mapping physics problem-solving skills using PhysProSS-CAT on the basis of the item response theory (IRT). The study was conducted inSleman Regency, Yogyakarta, involving 156 students of Grade XI of senior high school. Sampling was done using stratified random sampling technique. The results of the study show that the PhysProSS-CAT is able to accurately measure physics problem-solving skills. Students’ competences in physics problem solving can be mapped as 6% of the very high category, 4% of the high category, 36% of the medium category, 36% of the low category, and 18% of the very low category. This shows that the majority of the students’ competences in physics problem solving lies within the categories of medium and low.